2018
DOI: 10.1080/15476286.2018.1474074
|View full text |Cite
|
Sign up to set email alerts
|

Recoding of the selenocysteine UGA codon by cysteine in the presence of a non-canonical tRNACysand elongation factor SelB

Abstract: In many organisms, the UGA stop codon is recoded to insert selenocysteine (Sec) into proteins. Sec incorporation in bacteria is directed by an mRNA element, known as the Sec-insertion sequence (SECIS), located downstream of the Sec codon. Unlike other aminoacyl-tRNAs, Sec-tRNA is delivered to the ribosome by a dedicated elongation factor, SelB. We recently identified a series of tRNA-like tRNA genes distributed across Bacteria that also encode a canonical tRNA. These tRNAs contain sequence elements generally r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The two ORFs associating with the overlapping selBC gene were named ORF1 and ORF2 in this study. As reported previously [12], Methylophila spp. use a tRNA Sec with a non-canonical discriminator base A73 instead of G73.…”
Section: Trna Sec Remnant Is Encoded Inside the Selb Gene In Psymasupporting
confidence: 85%
See 1 more Smart Citation
“…The two ORFs associating with the overlapping selBC gene were named ORF1 and ORF2 in this study. As reported previously [12], Methylophila spp. use a tRNA Sec with a non-canonical discriminator base A73 instead of G73.…”
Section: Trna Sec Remnant Is Encoded Inside the Selb Gene In Psymasupporting
confidence: 85%
“…It is known that a megaplasmid pSymA of Sinorhizobium ( Rhizobium ) meliloti encode a fdoGHI (for FDH-O) and selABCD gene cluster [ 10 , 11 ]. In our previous study on non-canonical SelB sequences [ 12 ], it was found that Rhizobiales SelB sequences in the public databases are annotated to have a C-terminal extension compared to other bacterial SelB sequences ( Figure 1 A) [ 13 ]. In the present study, a careful analysis of these Rhizobiales SelB sequences was performed to reveal the possible reason.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli WT CysRS was purified as described previously (47). Site-directed mutagenesis was used to replace His with Asn at position 235 of E. coli CysRS.…”
Section: Protein Purificationmentioning
confidence: 99%
“…Plates were run in buffer containing 0.75 KH 2 PO 4 and 1 M urea for ϳ45 min. Sec (50 mM) was freshly prepared as described previously (49,50) tRNA aminoacylation assays E. coli tRNA Cys was transcribed in vitro using T7 RNA polymerase and labeled at the 3Ј-end adenosine with [ 32 P]phosphate as described previously (47,51). Aminoacylation experiments were carried out in buffer containing 50 mM HEPES (pH 7.3), 10 mM ATP, 2 mM DTT, 10 mM MgCl 2 , 50 mM KCl, 20 M E. coli tRNA Cys (containing trace amounts of 32 P-labeled tRNA), and varying concentrations of Sec and Cys (3-600 M).…”
Section: Atp-pp I Exchange Assaysmentioning
confidence: 99%
“…Fu et al reviewed the underlying molecular biology of translation with selenocysteine and they address challenges associated with engineering designer selenoproteins [7]. In a related study, Vargas-Rodriguez et al uncovered an unusual or non-canonical tRNA Cys that co-opts the selenocysteine machinery to incorporate cysteine instead [8]. The authors characterized a novel tRNA Sec -like tRNA Cys from Desulfotomaculum nigrificans that recodes UGA codons with cysteine instead of selenocysteine and dubbed this new molecule tRNA ReC to indicate its ability to recode with cysteine.…”
Section: Trnas For Synthetic Biologymentioning
confidence: 99%